PERBANDINGAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK DAN STAD BERBASIS IT MATERI OPERASI HITUNG BILANGAN BULAT SISWA KELAS VII SMP NEGERI 2 BANYUBIRU - Idza Nur Haida; Tri Nova Hasti Yunianta (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2018)
This study aims to determine the differences and comparisons of mathematics learning result using the talking stick cooperative learning model and STAD (Student Teams Achievement Division) based on IT with number operation lesson for grade VII students of SMP Negeri 2 Banyubiru. This research model is a quasi-experimental research using cluster random sampling technique. Data collection instruments in this study consisted of instruments of teacher observation sheets, instruments test and documentation. Both selected classes have been ascertained homogeneous before being treated. Analysis of the final activity data shows the average learning outcomes of mathematics on learning the talking stick type is 91.88 higher than the STAD type learning model which is 84.84. The results of hypothesis testing using the Mann-Whitney U test produce sig values. (2 tailed) 0.020 <0.05 it can be concluded that the two learning models applied have different learning result in mathematics.